The fate and function of the Arabidopsis Class I formin AtFH1 during central vacuole biogenesis in the rhizodermis - Kočová, Helena; Žárský, Viktor; Cvrčková, Fatima (Frontiers in Plant Science, 2025)
IntroductionDuring plant cell differentiation, major restructuring of endomembranes takes place, resulting in the formation of the large central vacuole. We previously reported that the Arabidopsis Class I formin AtFH1 (At3g25500), a member of a plant-specific family of cytoskeletal organizers that are at the same time integral membrane proteins, transiently localizes to the tonoplast in the root transition zone around the time of central vacuole consolidation.MethodsWe used in vivo fluorescent protein expression in combination with pharmacological treatments and quantitative image analysis to examine the behavior and role of AtFH1 during central vacuole formation.ResultsThe protein was found to enter the vacuole lumen in the root elongation zone and some shoot tissues, suggesting that its brief residence at the tonoplast in the transition zone is also an intermediate of a process leading to its vacuolar degradation. However, impairment of AtFH1 function by mutations or by the formin inhibitor SMIFH2 resulted in altered vacuole organization, while only the loss-of-function mutations affected rapid, cytoplasmic streaming-related tonoplast motility.DiscussionThese observations suggest that tonoplast-associated AtFH1 may act as an active cargo that affects tonoplast organization while on the way toward being degraded.